2015
DOI: 10.1021/acs.est.5b02341
|View full text |Cite
|
Sign up to set email alerts
|

Rates of As and Trace-Element Mobilization Caused by Fe Reduction in Mixed BTEX–Ethanol Experimental Plumes

Abstract: Biodegradation of organic matter, including petroleum-based fuels and biofuels, can create undesired secondary water-quality effects. Trace elements, especially arsenic (As), have strong adsorption affinities for Fe(III) (oxyhydr)-oxides and can be released to groundwater during Fe-reducing biodegradation. We investigated the mobilization of naturally occurring As, cobalt (Co), chromium (Cr), and nickel (Ni) from wetland sediments caused by the introduction of benzene, toluene, ethylbenzene, and xylenes (BTEX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Arsenic-enriched sediment at ~20 m depth provides a source of As to the aquifer. Batch sediment incubations showed that the arsenic in this zone undergoes reductive dissolution, especially when stimulated by glucose addition (Figure 7 From the Jianghan plain, we surmise that As concentrations are altered by human activities changing subsurface hydrology and chemistry; land use changes that may alter arsenic include pond excavation (Neumann et al, 2010), groundwater extraction, and infiltration of organic compounds (Ziegler et al, 2015). Likewise, continued monitoring of As concentrations used for drinking and irrigation is necessary across Asia as we continue to understand the complex mechanisms leading to As contamination in Asian groundwater.…”
Section: Discussionmentioning
confidence: 89%
“…Arsenic-enriched sediment at ~20 m depth provides a source of As to the aquifer. Batch sediment incubations showed that the arsenic in this zone undergoes reductive dissolution, especially when stimulated by glucose addition (Figure 7 From the Jianghan plain, we surmise that As concentrations are altered by human activities changing subsurface hydrology and chemistry; land use changes that may alter arsenic include pond excavation (Neumann et al, 2010), groundwater extraction, and infiltration of organic compounds (Ziegler et al, 2015). Likewise, continued monitoring of As concentrations used for drinking and irrigation is necessary across Asia as we continue to understand the complex mechanisms leading to As contamination in Asian groundwater.…”
Section: Discussionmentioning
confidence: 89%
“…First, Mn and Fe oxides in soils and sediments strongly sorb many cations [31]. In particular, As has strong adsorption affinities for reduced Fe species, Fe (III) oxyhydroxides, and can be released to groundwater during Fe-reducing biodegradation [32]. When these oxides are reduced, any sorbed cations are mobilized [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a number of transformation products resulting from the degradation of organic substances are present in flowback/produced waters such as organic acids, acetate, and halogenated compounds. , The biodegradation of these organic compounds can produce secondary water quality impacts, similar to those produced by CH 4 oxidation (section ) (Figure ). For example, an experimental injection study showed that the biodegradation of BTEX and ethanol coupled with Fe reduction released naturally occurring As, Co, Cr, and Ni to groundwater . Moreover, groundwater depletion may occur in shale gas areas where large volumes of groundwater are withdrawn for hydraulic fracturing. , The associated water table decline increases the exposure of aquifer minerals to O 2 , which diffuses through the water-unsaturated zone.…”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%